2013
DOI: 10.1016/j.annepidem.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio, poverty, and concurrent partnerships among men and women in the United States: a multilevel analysis

Abstract: Purpose Social and economic contextual factors may promote concurrent sexual partnerships, which can accelerate population HIV/STI transmission and are more common among African Americans than U.S. Whites. We investigated the relationship between contextual factors and concurrency. Methods We analyzed past-12-month concurrency prevalence in the 2002 National Survey of Family Growth and its contextual database in relation to county sex ratio (among respondent’s racial/ethnic group), percentage in poverty (amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 21 publications
6
70
1
5
Order By: Relevance
“…For example, Angrist found that, among immigrants to the USA, high sex ratios had a large positive effect on the likelihood of female marriage and a large negative effect on female labor force participation; with men providing investment, women could avoid wage labor [37]. In general, malebiased sex ratios are associated with a greater proportion of males being married [34,38], less promiscuity in both sexes [36,39,40], and greater conjugal stability [41], all of which might contribute to the lower I s values for men shown in Box 2.…”
Section: Box 1 Changing the Direction Of The Causal Arrow Between Pimentioning
confidence: 99%
“…For example, Angrist found that, among immigrants to the USA, high sex ratios had a large positive effect on the likelihood of female marriage and a large negative effect on female labor force participation; with men providing investment, women could avoid wage labor [37]. In general, malebiased sex ratios are associated with a greater proportion of males being married [34,38], less promiscuity in both sexes [36,39,40], and greater conjugal stability [41], all of which might contribute to the lower I s values for men shown in Box 2.…”
Section: Box 1 Changing the Direction Of The Causal Arrow Between Pimentioning
confidence: 99%
“…Place characteristics, such as rates of poverty, violent crime, incarceration, and male to female sex ratios are thought to be powerful drivers of sexual behaviors and HIV/STI risk, particularly among U.S. black adults. [19][20][21][22][23][24][25] Past studies have used a variety of approaches to recruiting high risk women into prospective HIV cohort studies in the United States, such as peer referrals, self-referrals (e.g., flyers), and clinic-based recruitment. 6,9,[26][27][28][29] Methodologies that recruit participants from community settings may be a particularly promising approach to finding women at elevated risk of HIV and to engage them in the research process.…”
Section: Introductionmentioning
confidence: 99%
“…Ecologic studies suggest that STI prevalence is elevated in areas that have higher levels of poverty, social disorder, incarceration, or racial/ethnic residential segregation. e.g.,1,2 Multilevel studies of people nested in places have corroborated these ecologic findings e.g.,3-6 and have expanded exposures to include male:female sex ratios 7-9 and expanded outcomes to include sexual behaviors. e.g., 7-9 All but two of these multilevel studies, however, have been cross-sectional.…”
Section: Introductionmentioning
confidence: 99%
“…e.g.,1,2 Multilevel studies of people nested in places have corroborated these ecologic findings e.g.,3-6 and have expanded exposures to include male:female sex ratios 7-9 and expanded outcomes to include sexual behaviors. e.g., 7-9 All but two of these multilevel studies, however, have been cross-sectional. 3,8 Ecologic and cross-sectional studies have limited ability to establish causal relationships between neighborhood-level exposures and STIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation